DIMENSIONS OF THE FIVE-FACTOR PERSONALITY MODEL: IMPLICATION OF COACH BURNOUT IN TRAINING PROCESSES - Miroljub Ivanović; Irina Ćosić (Sport Scientific And Practical Aspects, 2026)
The aim of this cross-sectional study was to test the predictive intensity of perceived global and socially adaptive basic personality dimensions in predicting the variability of the work burnout construct among sports coaches. The pertinent sample included 282 coaches from Serbian sports clubs (Mage = 38.15, SD = 0.427). Two measuring instruments were applied via the online model: the Big Five Inventory (BFI) and Burnout Assessment Tool (BAT). The tested independent variables of global personality, with adequate standard errors of the β coefficient, explain from 17% to 28% of the total variance of the global personality dimension, while socially adaptive personalities predict from 21% to 30% of the total variability of the burnout syndrome criteria. The partial predictor conscientiousness is a negative determinant of the dependent variable of impaired cognitive functioning. In addition, the factors agreeableness and extraversion are negative determinants of the detachment criterion, extraversion is a negative determinant of the exhaustion criterion, while the predictor conscientiousness is a negative determinant of the construct of impaired cognitive functioning. The obtained scores are a relevant foundation for the operationalization of further research, as well as guidelines for further research and practical implications for coach burnout during training processes.